SPEECH ACTS ANALYSIS IN COLLEGE DISCOURSE AT THE ENGLISH DEPARTMENT OF MUHAMMADIYAH UNIVERSITY OF MATARAM IN ACADEMIC YEAR 2016/2017 - Muhammad Fauzi Bafadal (Linguistics and ELT Journal, 2017)
In expressing something, speakers showed an action. This action could make the listeners easier to know what the speakers intended to. This is called speech act. The purpose of this research was to analyze the types of speech act used in college discourse at the English departement of Muhammadiyah University of Mataram. The researcher used those speeches as the data. The researcher took 14 students of English departement at Muhammadiyah University of Mataram as the participants. Observation was used as the data collection procedure. The result of research revealed that the aspects of speech act used at the college discourse analyzed by the researcher were: locutionary act, illocutionary act, and perlocutionary act. From those three aspects analyzed by the researcher, illocutionary act was the most often used in college discourse at the English departement of Muhammadiyah University of Mataram.